Shake-table experiment on reinforced concrete structure containing masonry infill wall. - Hashemi, Alidad
A hypothetical 5-storey prototype structure with reinforced concrete (RC) frame and unreinforced masonry (URM) wall is considered. The paper focuses on a shake-table experiment conducted on a substructure of this prototype consisting of the middle bays of its first storey. A test structure is constructed to represent the selected substructure and the relationship between demand parameters of the test structure and those of the prototype structure is established using computational modelling. The dynamic properties of the test structure are determined using a number of preliminary tests before performing the shake-table experiments. Based on these tests and results obtained from computational modelling of the test structure, the test ground motions and the sequence of shakings are determined. The results of the shake-table tests in terms of the global and local responses and the effects of the URM infill wall on the structural behaviour and the dynamic properties of the RC test structure are presented. Finally, the test results are compared to analytical ones obtained from further computational modelling of the test structure subjected to the measured shake-table accelerations.
Keywords: Earthquakes; Infilled frame; Modelling; Reinforced concrete; Shake-table.; URM wall